Analisis Dampak Kebijakan Ekonomi terhadap Pendapatan, Ketimpangan, dan Kemiskinan di Indonesia: Suatu Tinjauan Pustaka Economic Development oleh Michael P. Todaro dan Stephen C. Smith - Sodik, Gugun; Riantani, Suskim (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2026)
This study aims to review and analyze the impact of economic policies on income, inequality, and poverty in Indonesia, utilizing concepts from the book Economic Development by Michael P. Todaro and Stephen C. Smith. Theories and development approaches put forth by Todaro and Smith, such as the Kuznets Curve, multidimensional poverty, and pro-poor policies, serve as the framework for evaluating the effectiveness of economic policies in Indonesia. This study employs a qualitative descriptive approach through a literature review, focusing on fiscal, monetary, and social programs. The results indicate that economic policies in Indonesia have positively impacted income growth and reduced economic inequality, although their effectiveness varies depending on policy implementation. Redistribution policies, such as social assistance and subsidies, have proven effective in reducing poverty levels, consistent with the multidimensional poverty approach suggested by Todaro and Smith. However, challenges related to equitable distribution and accessibility in remote areas remain significant obstacles to achieving inclusive development. This study concludes that Indonesia's economic policies generally align with the development theories presented by Todaro and Smith, but further efforts are needed to enhance policy implementation and effectiveness. Recommendations are provided to improve the distribution of social assistance and increase access for vulnerable groups in order to achieve more sustainable and inclusive development. Keywords: economic policy, income, inequality, poverty, literature review, Todaro and Smith, Indonesia.